2021
DOI: 10.1155/2021/6832188
|View full text |Cite
|
Sign up to set email alerts
|

Calculation Model of Shear Capacity of Multiple Composite Core Column Joints Based on Softened Tension‐Compression Bar Model

Abstract: This paper aims to study the seismic performance of multiple composite core column joints. The influence of the stress mechanism, axial compression ratio, and shear span ratio on the failure mode, hysteretic performance, and shear capacity of the multiple composite core column joints was studied through the low-reversed cyclic loading tests of three specially designed and manufactured multiple composite core column joints. The angle ratio method is used to calculate the effective area of the vertical tie bar, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…where A str is the cross-section area of the baroclinic bar; θ is the angle between the baroclinic bar and bottom longitudinal bar (θ � arctan(h ′ b /h ′ c ), h ′ b , and h ′ c are the spacing of longitudinal bars in the protective layer of beam and column, respectively) It is found that compressive stress diffusion exists in the process of force transmission of steel fiberreinforced concrete baroclinic bar [24]. To simplify the calculation, the effective cross-sectional area of the baroclinic bar is determined by the following formula:…”
Section: Calculation Model Of Shear Capacity Of Recycled Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…where A str is the cross-section area of the baroclinic bar; θ is the angle between the baroclinic bar and bottom longitudinal bar (θ � arctan(h ′ b /h ′ c ), h ′ b , and h ′ c are the spacing of longitudinal bars in the protective layer of beam and column, respectively) It is found that compressive stress diffusion exists in the process of force transmission of steel fiberreinforced concrete baroclinic bar [24]. To simplify the calculation, the effective cross-sectional area of the baroclinic bar is determined by the following formula:…”
Section: Calculation Model Of Shear Capacity Of Recycled Steelmentioning
confidence: 99%
“…In the nishing formula (24), taking μ α 1 η b f ft cos θ 2 /sin θ 1 , the shear capacity V rf of recycled steel bers is…”
Section: Calculation Model Of Shear Capacity Of Recycled Steelmentioning
confidence: 99%